Performance analysis of bifacial PV module based multilevel solar panel system for urban areas - Anjum, Akib; Tanveer, Anamul Hassan; Arefin, Anwarul; Sikder, Maidul Kabir (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2019.